Adverse events following yellow fever vaccination in immunocompromised persons - Amanda Nazareth Lara; Karina Takesaki Miyaji; Karim Yaqub Ibrahim; Marta Heloisa Lopes; Ana Marli Christovam Sartori (Revista do Instituto de Medicina Tropical de São Paulo, 2021)
ABSTRACT This observational retrospective study conducted during an yellow fever (YF) outbreak in Sao Paulo, Brazil, in 2017-2018, describes adverse events (AE) following YF vaccination of immunocompromised persons. Risks and benefits of vaccination were individually evaluated by physicians. AE were assessed by phone call or electronic mail, 14 to 90 days after vaccination. Three hundred and eighty one immunocompromised persons received a full-dose of YF vaccine. Their age ranged from 1.4 to 89.3 years (median 50.8 years); 53% were women; 178 (46.7%) had chronic kidney disease, 78 (20.5%) had immune-mediated inflammatory diseases; 94 (24.7%) were using or had recently used immunosuppressive/ immunomodulatory drugs. All of them denied previous YF vaccination. We were able to contact 341 (89.5%) vaccinees: 233 (68.3%) of them received the YF vaccine from BioManguinhos and 108 (31.7%) received the vaccine from Sanofi-Pasteur; 130 (38.1%) vaccinees received other vaccines (up to 4) simultaneously with the the YF vaccine, mostly hepatitis B (59 vaccinees), pneumococcal polysaccharide 23-valent (46), influenza (43) and diphtheria-tetanus (dT, 41). One hundred and eleven vaccinees (32.6%) reported at least one AE: 79 (23.2%) presented systemic AE, 44 (12.9%) had local AE and 12 had both, local and systemic AE. The most common AE was pain at the injection site (41 persons, 12%), myalgia (34; 10%), fever (25; 7.3%) and headache (16; 4.7%). There was no statistically significant difference on the AE frequency according to the vaccine producer. There were four severe AE: one hospitalization and three deaths, considered not related to the YF vaccine.